Valor razonable de las cuentas por cobrar y su impacto tributario - Doilet Feijoo, María Verónica (2023)
This research consists of preparing a report on the impact between the tax standard and IFRS 9 in the determination of the reasonable adjustment in the measurement of accounts receivable, in order to evaluate the tax impact generated by the measurement at fair value of the allowance for doubtful accounts, for unpaid credits from external customers of a security company in Guayaquil within one year. The first chapter highlights the importance of the titling issue and its contribution to security companies in the city of Guayaquil................